2011
DOI: 10.1210/en.2010-0782
|View full text |Cite
|
Sign up to set email alerts
|

KT5823 Differentially Modulates Sodium Iodide Symporter Expression, Activity, and Glycosylation between Thyroid and Breast Cancer Cells

Abstract: Na(+)/I(-) symporter (NIS)-mediated iodide uptake into thyroid follicular cells serves as the basis of radioiodine therapy for thyroid cancer. NIS protein is also expressed in the majority of breast tumors, raising potential for radionuclide therapy of breast cancer. KT5823, a staurosporine-related protein kinase inhibitor, has been shown to increase thyroid-stimulating hormone-induced NIS expression, and thus iodide uptake, in thyroid cells. In this study, we found that KT5823 does not increase but decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…We choose tRA/H-treated MCF-7 cells to investigate the effect of overexpression of miR-339-5p on the levels of endogenous h NIS mRNA and hNIS-mediated RAIU, as it is well established that tRA/H significantly induces the expression and function of hNIS in MCF-7 cells (Kogai et al . 2000, Beyer et al . 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We choose tRA/H-treated MCF-7 cells to investigate the effect of overexpression of miR-339-5p on the levels of endogenous h NIS mRNA and hNIS-mediated RAIU, as it is well established that tRA/H significantly induces the expression and function of hNIS in MCF-7 cells (Kogai et al . 2000, Beyer et al . 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The lower molecular mass of hypoglycosylated NIS suggests that KT5823 has a similar effect on glycosylation to brefeldin A, an inhibitor of protein transport from the ER to the Golgi apparatus. The effect of decreased iodide uptake in experimental KT5823-treated breast cancer cell mutants with single or triple mutations of NIS glycosylation sites (N225Q, N489Q, N502Q, N225Q/N489Q/N502Q) showed that the inhibition of iodide uptake was only partly connected with hypoglycosylation of NIS [ 84 ].…”
Section: Glycosylation Of Proteins Involved In Thyroid Functioningmentioning
confidence: 99%
“…Membrane protein is generally produced in the endoplasmic reticulum, and then move to cellular membrane through the golgi complex. This membrane localization process requires proper protein post-translational modification including phosphorylation and glycosylation [ 16 , 17 ]. Levi et al .…”
Section: Introductionmentioning
confidence: 99%